A phase 1, placebo-controlled, randomized study of the safety, tolerability, and immunogenicity of a Clostridium difficile vaccine administered with or without aluminum hydroxide in healthy adults - Sheldon, Eric; Kitchin, Nicholas; Peng, Yahong; Eiden, Joseph; Gruber, William; Johnson, Erik; Jansen, Kathrin U.; Pride, Michael W.; Pedneault, Louise (Vaccine, 2016)
•Phase 1 study of a toxoid A and B vaccine in healthy adults aged 50–85 years.•Immunogenicity was present after Dose 2, with an anamnestic response at Month 7.•Response was higher in the toxoid-only groups than in the Al(OH)3-containing groups.•No clear dose response was evident in either the 50–64-year or 65–85-year cohort.•Magnitude of the immune response was similar in the 2 age cohorts.•Most common local reactions and systemic events were injection site pain, headache and fatigue. Clostridium difficile is a significant cause of morbidity and mortality in hospitals, nursing homes, and long-term care facilities. The bacteria can produce 3 toxins, of which the C. difficile toxin A and C. difficile toxin B are the principal virulence factors for C. difficile-associated disease. A phase 1, first-in-human, placebo-controlled, dose-escalation study was performed to assess the safety and immunogenicity of an investigational vaccine candidate consisting of genetically and chemically detoxified, purified toxins A and B. The toxoids, either alone or in combination with aluminum hydroxide (Al(OH)3), were administered to healthy adults 50–85 years of age at antigen dose levels of 50, 100, or 200μg in a 3-dose regimen administered at 0, 1, and 6 months. Overall, the C. difficile vaccine formulations and doses administered were generally well tolerated. Local reactions and systemic events were predominantly mild to moderate, were more common in the 50–64-year age cohort, and comprised mostly injection site pain, headache, and fatigue. In subjects who received the vaccine formulations, both the toxin A- and toxin B-specific neutralizing antibody geometric mean concentrations increased substantially at 1 month after Dose 2 and after Dose 3 compared to baseline. In the 50–64-year age cohort, geometric mean fold rises (GMFRs) in toxin A-specific neutralizing antibodies from baseline at Month 7 ranged from 59.19 to 149.23 in the vaccine groups compared to 2.47 in the control group. For toxin-B specific neutralizing antibodies, the GMFRs from baseline at Month 7 ranged from 116.67 to 2503.75 in the vaccine groups compared to 2.48 in the control group. In the 65–85-year age cohort, GMFRs in toxin A-specific neutralizing antibodies from baseline at Month 7 ranged from 42.73 to 254.77 in the vaccine groups compared to 2.03 in the control group. For toxin-B specific neutralizing antibodies, the GMFRs from baseline at Month 7 ranged from 136.12 to 4922.80 in the vaccine groups compared to 1.58 in the control group. Potent antitoxin neutralizing responses were still evident in immunized subjects in both age groups at Month 12. Although there was no clear dose-level response pattern, the data suggest that both the antitoxin A- and B-specific neutralizing responses were trending higher in the toxoid-only groups compared to the toxoid+Al(OH)3 groups. Furthermore, the magnitude of the immune response was similar in the 2 age cohorts. The vaccine formulations studied in this phase 1 study were immunogenic and well tolerated. The results presented support further development of the C. difficile vaccine candidate in a larger population of subjects to determine the optimal dose and immunization schedule. NCT01706367.